Rethinking the Theory of Change for Health in All Policies; Comment on "Health Promotion at Local Level in Norway: The Use of Public Health Coordinators and Health Overviews to Promote Fair Distribution Among Social Groups" - Ditte Heering Holt (Kerman University of Medical Sciences, 2018)
This commentary discusses the interesting and surprising findings by Hagen and colleagues, focusing on the role of the public health coordinator as a Health in All Policies (HiAP) tool. The original article finds a negative association between the employment of public health coordinators in Norwegian municipalities and consideration of a fair distribution of social and economic resources between social groups in local policy-making and planning. The commentary contemplates whether this surprising negative association should be interpreted as a failure of implementation, as suggested by the authors, or whether it might be the theory of change that has failed. On this basis, it is suggested that the very notion of HiAP could be flawed by the assumption that health should function as an overarching aim across government sectors. Potentially, the social determinants of health (SDH) might be more efficiently addressed by means of sectoral action by the corresponding sectors, emphasizing equity rather than health.